2014
DOI: 10.1016/j.jecp.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Category-specific face prototypes are emerging, but not yet mature, in 5-year-old children

Abstract: Adults' expertise in face recognition has been attributed to norm-based coding. Moreover, adults possess separable norms for a variety of face categories (e.g., race, sex, age) that appear to enhance recognition by reducing redundancy in the information shared by faces and ensuring that only relevant dimensions are used to encode faces from a given category. Although 5-year-old children process own-race faces using norm-based coding, little is known about the organization and refinement of their face space. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 75 publications
1
23
0
Order By: Relevance
“…Indeed, available evidence indicates that, although children represent faces in a multidimensional face space that has some adult-like characteristics at least from the age of 4 years (Jeffery et al, 2010), considerable refinement of this representation occurs throughout childhood. For example, separable representations of faces belonging to different categories defined by race, gender, and age emerge between 5 and 8 years of age (e.g., Short, Hatry, & Mondloch, 2011;Short, Lee, Fu, & Mondloch, 2014), and the representation of changeable facial traits like emotional expressions is also subject to critical changes across this same age range (Rodger et al, 2015). Other studies investigating identity discriminations have shown that, from 7 years onward, there are no differences between children and adults in the number of dimensions along which they represent faces, but children rely more heavily on one single dimension (e.g., hair cues or eye colour) when making similarity judgments, whereas adults use all dimensions equally (Nishimura et al, 2009;Pedelty, Levine, & Shevell, 1985).…”
mentioning
confidence: 99%
“…Indeed, available evidence indicates that, although children represent faces in a multidimensional face space that has some adult-like characteristics at least from the age of 4 years (Jeffery et al, 2010), considerable refinement of this representation occurs throughout childhood. For example, separable representations of faces belonging to different categories defined by race, gender, and age emerge between 5 and 8 years of age (e.g., Short, Hatry, & Mondloch, 2011;Short, Lee, Fu, & Mondloch, 2014), and the representation of changeable facial traits like emotional expressions is also subject to critical changes across this same age range (Rodger et al, 2015). Other studies investigating identity discriminations have shown that, from 7 years onward, there are no differences between children and adults in the number of dimensions along which they represent faces, but children rely more heavily on one single dimension (e.g., hair cues or eye colour) when making similarity judgments, whereas adults use all dimensions equally (Nishimura et al, 2009;Pedelty, Levine, & Shevell, 1985).…”
mentioning
confidence: 99%
“…Results also revealed that participants more often selected more average adult female faces than more average adult male faces, but that target sex difference was not consistently observed for 5-year-old and 9-year-old target faces [58]. This discrepancy might have occurred because children are in the process of forming more distinct representations for female and male faces and for adult and child faces [56,57]. Given early predominant experience with adult females for most children [18][19][20][21][22], the adult female face category average should be more established than the adult male face category average or child categories and thus most greatly influence averageness preferences for adult female faces.…”
Section: Middle Childhoodmentioning
confidence: 90%
“…Older children's increase in attention toward boys' attractiveness might be due to children's facial representations becoming more differentiated between 5 and 8 years of age. More specifically, 5-year-olds do not appear to have separate facial representations for female and male adult faces (or child and adult faces, or faces from different racial groups) [56]. [46,56] that are presumably attractive [12] and guiding processing of female and male targets' facial attractiveness (Figure 3).…”
Section: Middle Childhoodmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in face‐processing ability sometimes follow nonlinear developmental trajectories (e.g., Chung & Thomson, ; Leonard, Karmiloff‐Smith, & Johnson, ; Mondloch, Dobson, Parsons, & Maurer, ; Mondloch, Le Grand, & Maurer, ; Short, Lee, Fu, & Mondloch, ). Moreover, there is evidence both for and against qualitative shifts in face perception ability during childhood (see Want, Pascalis, Coleman, & Blades, ), and a transient disruption during adolescence (Carey, Diamond, & Woods, ; Diamond, Carey, & Back, ; Thomas, De Bellis, Graham, & LaBar, ) possibly due to pubertal hormones (see Scherf, Behrmann, & Dahl, ).…”
mentioning
confidence: 99%